2010
DOI: 10.1016/j.ijantimicag.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of genes for various extended-spectrum β-lactamases: a novel resistance strategy of Klebsiella pneumoniae in Poland

Abstract: Among 110 randomly sampled strains from a collection of 247 extended-spectrum beta-lactamase (ESBL)-producing clinical isolates of Klebsiella pneumoniae collected from hospitalised children in three paediatric hospitals in Poland, 64 strains (58.2%) with multiple ESBLs were found, including five non-clonal strains (4.5%) harbouring bla genes for ESBLs of three families (CTX-M, SHV and TEM). This is the first report of the emergence of triple ESBL-producing K. pneumoniae in Poland. In addition, K. pneumoniae st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…As in previous studies [25-27] the bla CTX-M-15 allele associated with ISEcp1 was carried on multiple conjugative plasmids of different sizes ranging from 25 kb-485 kb, with one clone having multiple copies of bla CTX-M-15 genes, one copy in the chromosome and two other copies in a 485 kb and a 25 kb plasmid This reflects transmission dynamics of this element, comprising of intra strain mobility on different genetic entities (chromosome, plasmids) within a single isolate, in addition to inter- strain and inter-species transmissibility. Multiple ESBL alleles were observed in which bla CTX-M-15 and bla SHV-11 co-existed in one clone in the neonatal unit; this has recently been described in clinical isolates in Poland as a new strategy of K. pneumoniae to confer resistance to antibiotics [28]. There is an antibiotic selection advantage for the isolates with multiple alleles and multiple copies of genes for an allele as seen in cluster X7 in this study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…As in previous studies [25-27] the bla CTX-M-15 allele associated with ISEcp1 was carried on multiple conjugative plasmids of different sizes ranging from 25 kb-485 kb, with one clone having multiple copies of bla CTX-M-15 genes, one copy in the chromosome and two other copies in a 485 kb and a 25 kb plasmid This reflects transmission dynamics of this element, comprising of intra strain mobility on different genetic entities (chromosome, plasmids) within a single isolate, in addition to inter- strain and inter-species transmissibility. Multiple ESBL alleles were observed in which bla CTX-M-15 and bla SHV-11 co-existed in one clone in the neonatal unit; this has recently been described in clinical isolates in Poland as a new strategy of K. pneumoniae to confer resistance to antibiotics [28]. There is an antibiotic selection advantage for the isolates with multiple alleles and multiple copies of genes for an allele as seen in cluster X7 in this study.…”
Section: Discussionsupporting
confidence: 55%
“…All outbreaks occurred in the neonatal unit and neonatal ICU at different time-points and could be due patient to patient transmission or the acquisition from a common source (contaminated equipments) or from healthcare workers [28-30]. Different clones were involved in all three outbreaks; this further supports the high diversity of these strains in this setting, and represents a huge challenge for the local hospital infection control team.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…90 kb that was similar to pCTX-M3 (11). Because pCTX-M3 carries a gene encoding CTX-M-3 ESBL, we carried out PCR assay with primers specific for the bla CTX-M gene family (6). All the isolates tested except for DM0267 were found to produce CTX-M-type ESBL (Table 1).…”
mentioning
confidence: 99%
“…These results suggest the existence of highly adapted populations of K. pneumoniae and E. coli able to acquire antimicrobial resistance genes since at least the early 1990s. The sudden decrease of TEM-4 producers in all countries where it had been reported for years (17,18,20,21,35,36) parallels the shift in the epidemiology of beta-lactamases that involves the emergence of CTX-M, KPC (class A), and NDM (class B) and the drop in TEM-ESBL producers (22). Comparative genomics studies recently demonstrated the existence of intraclonal variants with enhanced epidemicity that can successfully spread at the global level as H30 ST131 E. coli or ST258/ST11 K. pneumoniae within clonal group (CG) 258 (37)(38)(39).…”
mentioning
confidence: 86%